Zoysiagrass (Zoysia spp. Willd.) for European lawns: A review - Magni, Simone; Pompeiano, Antonio; Gaetani, Monica; Caturegli, Lisa; Grossi, Nicola; Minelli, Alberto; Volterrani, Marco (Italian Journal of Agronomy, 2017)
In Europe the cultivation of warm season turfgrasses was negligible until the beginning of the 90â€™s. A scientific approach to their cultivation started with field trials being installed in several locations in Italy starting from 1994. Adaptation to climatic condition and first screening of relative performance of cultivars were held as primary elements to assess in order to assist turf growers in introducing the different species and cultivars of zoysiagrass (Zoysia spp. Willd.) in the warm temperate regions of Mediterranean Europe. At a later stage, studies on zoysiagrass adaptation were extended as north as 45Â° parallel and, as slow establishment began to appear a major limitation of this turfgrass, an alternative establishment method and establishment pattern were investigated. As for other warm season turfgrasses winter dormancy is considered a major drawback and trials dealing with fall fertilisation and winter management have been carried out to support winter maintenance decisions. In recent years soccer playing characteristics have been determined on zoysiagrass, while preliminary research results indicate turf management through remotely sensed data as a promising technique for the years to come.